Naked peoples: rules and regulations - I. Watson (Law Text Culture, 1998)
I am writing about the law of this country now called Australia. Kaldowinyeri [the creation time or the dreamtime], in the beginning, the ancestors come to know law. The law is naked like the land and its people, it is raw. Raw law is unlike the colonial legal system which comprises of layer upon layer of rules and regulations. The law is raw. Law is birthed by the creation. And like the birthing of the people, the law was born naked. All law was at Kaldowinyeri naked. The law is filled with the spirit of creation. It is a law of the land for the peoples to know and to live by as the ancestors have.